AB1240 CAUSES AND ASSOCIATION OF DEATH IN SYSTEMIC LUPUS ERYTHEMATOSUS PATIENTS IN A TERTIARY REFERRAL UNIVERSITY HOSPITAL IN EGYPT. (June 2019) - Abdelrahman, Fatma Ibrahim; Mortada, Mohammed A.
Abstract : Background: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease with heterogeneous, multisystem involvements which can sometimes be severe and life threatening. Different causes of mortality have been described over different decades in SLE patients (1) . Objectives: To describe and analyze the causes of death in SLE patients and to identify the associated risk factors in Egypt. Methods: A retrospective study was conducted on the SLE patients who died in the period from January 2014 to November 2019 in the Zagazig University hospitals. We collected demographic and laboratory data for all patients including; age of onset of SLE, age at death, disease duration, systems affected, last reported disease activity using the Systemic Lupus Erythematosus Disease Activity Index (SLEDAI), treatment received immunosuppressive regimen (dose and duration) and the cause of death. Results: 41 SLE patients (33 female and 8 males) had died during period from January 2014 to November 2019 with mean age at onset (26.1±8.1), mean age at death (37.4±13.3), mean SLE duration (11.2±6.7) and mean SLEDAI (15.4±6.8). Majority of the dyed patients had lupus nephritis (87.8%), (26.8%) had neurophsycatric lupus, (14.6%) had SLE vasculitis. (31.7%) had APS, (29.2%) had ILD, (14.6%) had pneumonitis, (19.5%) had carditis, and (14.6%) had PAH. All these patients were on a median dose of prednisolone 10 (2.5-20) mg daily with median of 10 (4-24) years of steroids. 11 of these patients (26.8%) had a family history of SLE. 21(51.2%) of them had received intravenous cyclophosphamide during their with mean cumulative dose of (6.7±4.6) gm, 16 (39%) had received MMF, 5 (12.3%) had received cyclosporine and 9 (22%) had received azathioprine. As regard causes of death, serious infection particularly pulmonary infection was the most common cause of death in 16 patients (39%), followed by stroke in 8(19.5%) patients, renal failure in 7 (17.1%), pneumonitis in 3(7.3%), cancer in 3(7.3%), Disseminated Intravascular Coagulation (DIC) in 1 (2.4%), Macrophage Activating Syndrome (MAC) in 1 (2.4%), pancytopenia in 1 (2.4%) and one (2.4%) pregnant patient died from eclampsia in her third trimester with her fetus. The risk of death from serious pulmonary infections is higher in patients with ILD and pneumonitis (p<0.000). The risk of stroke is higher in SLE patients with APS (P=0.03) and neurophsycatric lupus (p= 0.002). Conclusion: pulmonary infections was the most common cause of death in SLE patients in a tertiary university hospital in Egypt. References: [1] Wu, X., Yang, M., Xie, Y. et al. Clin Rheumatol (2019) 38: 107. https://doi.org/10.1007/s10067-018-4259-z. Disclosure of Interests: None declared